“Green Economy “And Economic Security: Expectations And Reality (International Journal of Scientific Research and Management (IJSRM), 2021)
The development of a green economy and economic security are truly among the most discussed at the present time. However, the nature and degree of their discussions are sometimes so active and off scale that the causes or origins of these problems are forgotten. We are talking about global climate change and its, in most cases, negative impacts and manifestations on the economic condition and economic security of countries’ development. The transition to a green economy system implies the expectation of a more stable and environmentally sustainable degree of development. At the same time, such a transition requires a deep restructuring, first of all, of the energy sector of the countries’ economies. Despite the attractiveness of an environmentally friendly system of a green economy, today it is not possible for a complete and widespread transition to this economic system by most countries in the world. The problem is that, on the one hand, not all countries have the ability to replace fossil fuels in primary energy production with renewable sources due to their high cost, on the other hand, not all countries have “clean sources” of fuel and conditions for using alternative energy sources. Ultimately, there is a need to develop a long-term policy for a gradual and phased transition to a “green economy”, which will make it possible to realistically determine the time frame for such transition.